2011
DOI: 10.1007/s10266-010-0138-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tooth bleaching on shear bond strength of brackets rebonded with a self-etching adhesive system

Abstract: The purpose of this study was to ascertain the effects of tooth bleaching on the shear bond strength of orthodontic brackets rebonded with a self-etching adhesive system. A total of 39 premolars were collected and divided into three equal groups: in group 1 bracket bonding was performed without bleaching treatment; specimens in group 2 were bonded immediately after bleaching; and group 3 teeth were bleached, then immersed in artificial saliva and left for 7 days before bonding. The shear bond strength was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
4
6
0
Order By: Relevance
“…However, in their study, the use of 2 acid etchings before and after the bleaching procedures could have masked the enamel changes created by the bleaching agent. The ARI scores in the study by Uysal et al,27 however, were very similar to those obtained in the present study and other studies,3,9,22-26 showing that the failure site moves to the enamel-adhesive interface when the bleached surfaces are bonded immediately.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, in their study, the use of 2 acid etchings before and after the bleaching procedures could have masked the enamel changes created by the bleaching agent. The ARI scores in the study by Uysal et al,27 however, were very similar to those obtained in the present study and other studies,3,9,22-26 showing that the failure site moves to the enamel-adhesive interface when the bleached surfaces are bonded immediately.…”
Section: Discussionsupporting
confidence: 91%
“…This conclusion was supported by microscopic observation, which suggested that interaction between the resin and residual peroxide in the enamel influenced the bond-strength reduction 8. The results of a study by Abe et al26 were very similar to those of our study, but the authors chose a 1-week recovery period. After 1 week, SBSs were similar to, but slightly lower than, those in the nonbleached group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[20]. Campoy et al [21] reported a bond failure rate of 6.08% in their study using new brackets, Transbond Plus self-etching primer and Transbond XT adhesive.…”
Section: Discussionmentioning
confidence: 96%